Addressing Psychosocial Vulnerabilities Through Antenatal Care—Depression, Suicidal Ideation, and Behavior: A Study Among Urban Sri Lankan Women - Palfreyman, Alexis (Frontiers in Psychiatry, 2021)
An absence of data persists for common perinatal mental disorders and suicidal ideation and/or behaviors (SIB), particularly from low- and middle-income countries and from the antenatal period. Capitalizing on Sri Lanka’s strong antenatal platform, we identify the prevalence of antenatal depressive symptomology, lifetime- and current pregnancy SIB and their risk factors in women in urbanizing Sri Lanka, and present opportunities for improved antenatal detection of psychosocial vulnerabilities. One thousand antenatal women in Gampaha District were screened in 2016 using a novel three-part instrument. Prevalence and risk factors associated with depressive symptomology and SIB were explored using univariate, bivariate and logistic regression analyses. Past-week prevalence of antenatal depressive symptomology was high (29.6%). One in four women reported a lifetime history of SIB, while SIB during the current pregnancy was reported at 7.4%. Exposure to intimate partner violence and lifetime SIB emerged as the strongest correlates of both depressive and current-pregnancy SIB outcomes (p < 0.05). This study evidences the high prevalence of multiple psychosocial vulnerabilities in pregnant women in Sri Lanka and underscores the need for their improved comprehensive assessment. Given antenatal care’s high rates of use in Sri Lanka and in low- and middle-income countries in general, this study presents it as a promising mechanism through which to effectively screen for multiple psychosocial vulnerabilities, supporting early identification and intervention for at-risk women and their families.